UNDERSTANDING CONFLICT, VIOLENCE AND WAR IN AFRICA THROUGH AFRICAN LITERATURE: A PHILOSOPHICAL REFLECTION (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
Violence, conflict and war can easily form the tripod on which everything that is against human progress rests. They are seriously implicated in Africa’s lack of development and constant crises. The Nigeria-Biafra experience serves as an empirical illustration of this problem. To address this problem it is necessary to understand both its latent and obvious causes. Getting behind an issue to understand its root causes as well as its evident manifestations can best be handled by disciplines that are equipped to study phenomena from a comprehensive outlook. This study identifies philosophy and African literature as having such capacity and as such employs them as its methodological tools. The study also explores how understanding conflict, violence and war in Africa, through African literature, on the one hand, and the philosophical interrogation of that understanding on the other hand, can be mutually rewarding. This study’s specific interest is on a novel, Half of a Yellow Sun, by a Nigerian writer, Chimamanda Ngozi Adichie could be of essence in peaceful coexistence. The book is based on the Nigeria-Biafra war of 1967-70. This study finds that the war has become an intractable event and an essential key to understanding developments and socio-political events in Nigeria. It concludes that until the difficult question of the place the Igbo people occupy in Nigeria’s national psyche is addressed with the seriousness, commitment, justice and equity it demands, Nigeria will continue to be susceptible to violence, conflict and (although it should never be allowed to repeat again) the possibility of another war.
Keywords: Conflict,Violence,War,AfricanLiterature,Philosophy